1982
DOI: 10.1037/h0088451
|View full text |Cite
|
Sign up to set email alerts
|

Clinical judgment in geropsychology practice.

Abstract: An empirical study utilizing an attribution paradigm was performed with 418 clinical psychologists. Therapists were mailed a ' 'clinical judgment" survey containing a standard case history varied according to age (46/72), class (working/middle) and gender; each therapist received only one of these eight possible combinations. Clients were rated along Likert scales on dependent variables tapping attitudinal (e.g., "usefulness of intervention"), symptomatological (e.g., "disorientation") and diagnostic dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Gender bias was not present for predicting who would be rehospitalized within 2 years (Stack et al, 1983) and for predicting suicide or compliance with treatment (Lewis et al, 1990). Also, in many studies, prognoses for male and female clients were not significantly different (Adams & Betz, 1993; Bernstein & Lecomte, 1982; Billingsley, 1977; Dailey, 1980; Fischer et al, 1976; Foon, 1989; Lewis et al, 1990; Lopez et al, 1993; Rabinowitz & Lukoff, 1995; Schwartz & Abra‐mowitz, 1975; Settin, 1982; Stearns et al, 1980; Wrobel, 1993; Zygmond & Denton, 1988). When the effect of gender was significant, prognostic ratings were more favorable for female clients than male clients, even though clients were described by the same case histories except for the designation of gender (Agell & Rothblum, 1991; Fernbach et al, 1989; Hansen & Reekie, 1990; Teri, 1982).…”
Section: Gender Biasmentioning
confidence: 99%
See 3 more Smart Citations
“…Gender bias was not present for predicting who would be rehospitalized within 2 years (Stack et al, 1983) and for predicting suicide or compliance with treatment (Lewis et al, 1990). Also, in many studies, prognoses for male and female clients were not significantly different (Adams & Betz, 1993; Bernstein & Lecomte, 1982; Billingsley, 1977; Dailey, 1980; Fischer et al, 1976; Foon, 1989; Lewis et al, 1990; Lopez et al, 1993; Rabinowitz & Lukoff, 1995; Schwartz & Abra‐mowitz, 1975; Settin, 1982; Stearns et al, 1980; Wrobel, 1993; Zygmond & Denton, 1988). When the effect of gender was significant, prognostic ratings were more favorable for female clients than male clients, even though clients were described by the same case histories except for the designation of gender (Agell & Rothblum, 1991; Fernbach et al, 1989; Hansen & Reekie, 1990; Teri, 1982).…”
Section: Gender Biasmentioning
confidence: 99%
“…However, in most of the studies published in the last 20 years, lower‐class subjects have not been diagnosed as having more severe mental disorders than middle‐class or upper‐class clients. This has been true when clinicians have been given case history information (Bamgbose et al, 1980; Franklin, 1985; Hardy & Johnson, 1992; Settin, 1982; Sutton & Kessler, 1986; Umbenhauer & DeWitte, 1978) and when they have been given case history information and IQ scores (Amira et al, 1977). Studies reporting nonsignificant social class effects have employed larger clinician sample sizes than studies reporting significant social class effects (an average clinician sample size of 266 vs. an average clinician sample size of 49).…”
Section: Social Class Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…The correlation is especially significant for older age groups in that pervading negative and fatalistic attitudes to deterioration and cognitive impairment may result in less psychological help being offered. Settin (1982) demonstrated this when he showed that a perceived lack of potential for psychological growth led to a denial of therapeutic aid and subsequent deterioration. In the present climate, where all age groups suffering mental distress must compete for services, older people frequently lose out.…”
Section: Providing Resourcesmentioning
confidence: 99%